A knowledge diffusion model of substitutive knowledge for evaluating the change of enterprise benefits. (1st January 2012) - Kreng, Victor B.; Tsai, Chih Ming
Since knowledge is difficult to be quantified due to its intangible characteristics of diffusion, depreciation, growth, and substitution with time; how to identify the change of knowledge value has become a crucial issue for enterprises. For this purpose, the knowledge diffusion model of the substitutive knowledge, which is based on the activity-based costing (ABC) model and the diffusion model of single knowledge, is presented to evaluate the changes of knowledge value and its corresponding enterprise benefits. Various parameters are considered simultaneously in the proposed model to illustrate many particular dimensions regarding knowledge management. In order to enhance the rationality and practicability, an electronic company in Taiwan is adopted as a case study. The results indicate that such model can appropriately describe the relationships between knowledge value and enterprise benefits. Therefore, intangible knowledge can be studied by means of analysing the parameters involved in the proposed model. The change of each parameter can also be used to demonstrate the performance of executing knowledge management.